FACTORS THAT AFFECT UNDERPRICING DURING THE INITIAL PUBLIC OFFERING ON IDX - Nugraheni, Irma Christiawati; Salim, Susanto (International Journal of Application on Economics and Business, 2023)
This study intends to examine the impact of ownership retention, company age, company size, and board commissioner independence on the degree of underpricing during an initial public offering (IPO) on the Indonesia Stock Exchange (IDX) in 2019–2021. Quantitative information from the company's financial records and the prospectus it published before an initial public offering (IPO) is used in this study. 143 businesses, chosen using the purposive selection method, made up the sample for this study. Application SPSS version 26 is used for the test. According to the study's findings, the ownership retention variable significantly and negatively affects IPO underpricing. On the other hand, IPO underpricing is positively and considerably impacted by firm size. On the other hand, IPO underpricing is positively and considerably impacted by firm size. A significant impact was not seen in this analysis for the factors board commissioner size, board independence, or company age.